The case for U.S. nuclear weapons in the 21st century - Roberts, Brad (Stanford University Press, 2016)
The book ultimately argues in favor of patience and persistence in the implementation of a balanced approach to nuclear strategy that encompasses political efforts to reduce nuclear dangers along with military efforts to deter them.